Self-compassion and Empathic Concerns as Correlates of Prosocial Behaviour Among Youths in Awka Metropolis - Obi, C.U.; Anyaegbunam, Michael; Nweke, K.O; Ifedigbo, C.F; Nwakasi, C (Practicum Psychologia, 2024)
This study investigated self-compassion and empathic concern as correlates of prosocial behavior among youths in Awka metropolis. A total of 188 participants were systematically drawn from a list of youths who applied for the Anambara state small scale business start up loan at the Ministry of Spots and Youth Empowerment who reside in Awka metropolis. 81 of the participants were male while 107 were females. They included 89 students, 34 civil servants, 42 self employed and 15 unemployed. The age of the participants ranged from 19 to 35 years with the mean age of 22.7 and a standard deviation of 4.35. Three instruments were used for data collection, namely: Self-compassion Scale (SCS), Empathic Subscale of the Interpersonal Reactivity Index (IRI) and Self Report Altruism scale (SRAS). Correlational design and Pearson Product Moment Correlation Analysis were used for design and appropriate statistics respectively. The result revealed that: a) a positive significant relationship between self compassion and prosocial behavior r=.58, p<.05; b) a positive significant relationship between empathic concern and prosocial behavior at r=.17, p<.05. Based on the findings, it was recommended that parents, religious leaders and other religious agents of socialization should set examples and also get youths to engage in various practical community services in order to help inspire them to participate in helping.